1969
DOI: 10.1111/j.1432-1033.1969.tb19596.x
|View full text |Cite
|
Sign up to set email alerts
|

Klassifizierung der Pullulanase als Exoenzym mit Hilfe der Gaschromatographie1

Abstract: Pullulanase from Aerobacter aerogenes is a glucosidase specifically splitting a-1,6-glycosidic bonds. A polymeric substrate for the pullulanase is the linear a-glucan pullulan from Pullularia This a-glucan consists of maltotriose units linked together by a-l,6-glycosidic bonds. This means that the polysaccharide is degraded by pullulanase to yield exclusively maltotriose. There are two possibilities of enzyme action : a) either the hydrolysis starts from one end of the linear chain directly setting free maltot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Subsequently the reverse reaction takes place thereby yielding either the a-or #?-pyranose or the a-or #?-furanose. Since the velocity of the ring closure is greater than the velocity of the ring opening by the factor lo4 [28] virtually no acyclic open aldehyde dissociates from the active center as has been shown by our polarographic experiments [5].…”
Section: The Mechanism Of the Enzymatically Catalyzed Mutarotationsupporting
confidence: 77%
See 2 more Smart Citations
“…Subsequently the reverse reaction takes place thereby yielding either the a-or #?-pyranose or the a-or #?-furanose. Since the velocity of the ring closure is greater than the velocity of the ring opening by the factor lo4 [28] virtually no acyclic open aldehyde dissociates from the active center as has been shown by our polarographic experiments [5].…”
Section: The Mechanism Of the Enzymatically Catalyzed Mutarotationsupporting
confidence: 77%
“…Earlier investigations had shown that the enzymatic catalysis of mutarotation by mutarotase from appears to follow a bifunctional mechanism as well [5]. I n this paper we are now presenting a detailed investigation of the mechanism of action of the functional groups of this enzyme.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The availability of highly purified preparations of pullulanase from Aerobacter aerogenes [5] has made this enzyme invaluable in the analysis of the fine structure of amylopectin [6]. Pullulanase, however, is of limited use in the analysis of glycogen structure because, although it is able to hydrolyse some branch linkages in degraded glycogen, it has little or no action on the undegraded macromolecule [7].…”
Section: Introductionmentioning
confidence: 99%
“…in 5 ml of 0.01 M acetate buffer, pH 5.4, was added 2 ml of Aerobacter pullulanase 6 ) containing 500 total units of activity, and a portion of the digest incubated for 24 hr at 40°C was subjected to chromatography on a column of Sephadex G-75 (¢ 2.0 x 55 cm) in which the dextrins produced were separated into two peak fractions: one was eluted at around the void volume zone of the column with a yield of 70%, and the other significantly later with a yield of 30 %. The former fraction seemed to be a mixture of slight hydrolysis products of the ,B-limit dextrin.…”
mentioning
confidence: 99%